Plant regulators for rooting of hardwood cuttings of blackberry plants cv. Xavante - Maia, Aline José (2008)
Aiming to evaluate the use of plant regulators for rooting of hardwood cuttings of blackberry cv. Xavante, two experiments were carried out in a greenhouse. In the first one the concentrations of indolil butyric acid varied in 0, 1000, 1500, 2000, 2500 and 3000 mg L-1. And in the second one, the plant regulator that was used was paclobutrazol at the concentrations of 0, 200, 400, 600, 800 and 1000 mg L-1. For each experiment the base of the cuttings were dipped in the solutions for ten seconds. After that, the cuttings were planted in rigid plastic vases with sand and kept under intermittent misty system. The following variables were evaluated, 71 days after planting: percentage of rooted cuttings, percentage of callus presence, average length of roots, number of roots, fresh weight of roots, percentage of sprouting. The treatment of hardwood cuttings with 2000 mg L-1 IBA had the greatest percentage of rooting (60%). Nevertheless, the treatment with 1000 mg L-1 IBA attained already high rooting percentage (56%), with 96% of sprouted cuttings and 17.6 roots per cutting. Cuttings treated with PBZ presented greater callus presence but they did not root, thus it is not possible to recommend this product for rooting of blackberry plants cv. Xavante among the tested concentrations.